2018
DOI: 10.1097/nmd.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Severity of Psychological Distress Among Refugees With the Refugee Health Screener, 13-Item Version

Abstract: The recent inflow of refugees to Sweden has put pressure on health care as well as revealing a need for methods regarding assessment of refugees' mental health status. The present study investigated the use of the Refugee Health Screener (RHS; Hollifield et al., 2013) to distinguish among severity levels of symptoms of psychological distress in refugees. Refugees residing in asylum accommodations (n = 510) were screened with RHS-13, together with screeners for depression, anxiety, and posttraumatic stress diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 22 publications
3
47
6
Order By: Relevance
“…They also lend support to meta-analyses indicating that at least one in three refugees is likely impacted by symptoms of depression, anxiety and/or PTSD. 9 10 37 Our estimates of the prevalence of the different levels of psychological distress defined by Bjärtå and colleagues 31 suggest that the following treatment capacities have to be provided by the German healthcare system: Every tenth refugee is likely in urgent need of care, slightly more than one in ten further refugees is likely to require standard care following further evaluation, and one in five additional refugees have lower levels of distress requiring further assessment that might best be remedied through lower threshold psychosocial interventions. 37 38 For the sake of those in need, it is also imperative to reduce legal limitations to full access to the healthcare system for all asylum seekers, as is the case, for instance, in Austria and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also lend support to meta-analyses indicating that at least one in three refugees is likely impacted by symptoms of depression, anxiety and/or PTSD. 9 10 37 Our estimates of the prevalence of the different levels of psychological distress defined by Bjärtå and colleagues 31 suggest that the following treatment capacities have to be provided by the German healthcare system: Every tenth refugee is likely in urgent need of care, slightly more than one in ten further refugees is likely to require standard care following further evaluation, and one in five additional refugees have lower levels of distress requiring further assessment that might best be remedied through lower threshold psychosocial interventions. 37 38 For the sake of those in need, it is also imperative to reduce legal limitations to full access to the healthcare system for all asylum seekers, as is the case, for instance, in Austria and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“… 29 31 A later study validated further cut-off points for moderate symptoms levels indicative of a likely need for treatment and severe levels indicative of an urgent need for care (18 and 25 points, respectively). 31 …”
Section: Methodsmentioning
confidence: 99%
“…This study was performed as a part of the project AMIR (Assessment of Mental Health and Early Intervention for Refugees). Results from the full project have been reported previously [21,22]. An outline of the methods section is presented herein, and more detail is in previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed the RHS-13 [20] and the Patient Health Questionnaire-9 (PHQ-9) [24] for the current study. The Generalized Anxiety Disorder-7 (GAD-7) [25], the Primary Care PTSD-4 (PC-PTSD-4) [26], and the World Health Organization Quality of Life – Brief (WHOQOL-BREF) [27] were completed at the same time for the larger study reported elsewhere [21,22]. The questionnaires were administered in seven different languages (Arabic, Dari, Farsi, Tigrinya, Somali, English, and Swedish).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation